Investigation on the self-performance of young Holstein Friesian bulls, focused on body conformation, feed intake and live weight - Ulbricht, Karsten; Kovács, Attila Zoltán; Stefler, József (Acta Agraria Kaposváriensis, 2014)
On the basis of genetic relationships between the bull’s generation and that of his daughter’s the influence of performance parameters in Bull Breed Licensing from young AI sire candidates on performance traits of the offspring was analysed. In the former Central Sire Station Meißen-Korbitz (MASTERRIND GmbH) the performance data from 1.598 test bulls and data from 257.201 animals from offspring were included in this study. The heritability of the observed parameters of young bulls were STA stature (0.36), PW pelvic width (0.31), LW live weight (0.33), DATY dairy type (0.16), LEGS overall of legs (0.23) FA foot angle (0.12) and BOM body muscling (0.38). DFI daily feed intake (0.22) from the Bull Feed Intake Testing Program was also estimated. The genetic correlations were as follows: the effects on the exterior appearance of the offspring were moderate to high. In particular, the sire features STA (rg 0.60), DATY (rg 0.55), LEGS (rg 0.52), FA (rg 0.39) and PW (rg 0.34) showed a clear relationships to the offspring’s overall classification (CLAS). An impact on the laminitis (LAM) in the offspring could be anticipated based on the sire traits LEGS (rg -0.40) and DATY (rg 0.71). The genetic correlation between the bulls’ and their daughter’s performance parameters showed that the use of the information about young bull candidates has an influence on economic and functional performance of the progeny.